Ukrainian-Chinese Economic Relations in the Context of EU-China Relations: Perspectives on Post-War Development - Davydova, I. O.; Artyomova, A. V.; Uvarova, I. S. (Statistics of Ukraine, 2023)
This research provides a comprehensive analysis of Ukrainian-Chinese economic relations, focusing on the prospects for post-war development. It examines the process of post-war recovery in 1945 in Europe, emphasizing the significant role played by the Marshall Plan in stimulating economic revival. The study also investigates the dynamics of trade and economic relations between Ukraine and China from 2013 to 2021, analyzing trends in exports and the impact of external factors. During this period, there were notable developments in bilateral trade, reflecting the growing economic ties between the two nations. Ukrainian exports to China witnessed a steady increase, driven by the demand for agricultural products, metals, and other raw materials. Similarly, the share of Chinese exports in Ukraine’s overall trade portfolio expanded, indicating a strengthening trade relationship. Additionally, it explores the trade relationship between the European Union (EU) and China and identifies opportunities for Ukraine to become a strategic trade hub. The article contributes to the understanding of Ukrainian-Chinese economic cooperation, highlights challenges faced, and provides insights into potential pathways for future development. Due to the lack of official statistics in 2022 and considering the strategic goal of EU accession, we propose to examine the future Ukrainian-Chinese relations through the prism of EU-China trade relations. The EU is a significant exporter to China, supplying a wide range of goods, including machinery, equipment, vehicles, chemicals, pharmaceuticals, and agricultural products. Some EU countries, such as Germany, France, and the Netherlands, are traditional major exporters to China. The results of regression analysis using the gravity model indicate that the size of the economy, geographical distance, and trade openness are important factors influencing bilateral trade flows between the EU and China. The growth of the GDP of the EU and China contributes to the increase in trade volumes between them. However, there are issues such as trade imbalance, human rights compliance, and the impact of the “Belt and Road Initiative” on EU-China relations.